Robotic-assisted Kidney Transplantation With Simultaneous Bilateral Nephrectomies Is an Efficient, Feasible, and Safe Way to Manage Patients With Renal Failure Secondary to Adult Polycystic Kidney Disease. Issue 9 (5th August 2021) - Rofaiel, George; Molnar, Miklos Z.; Baker, Nicholas; Campsen, Jeffrey; Kim, Robin
Abstract : Kidney transplantation has become the standard of care for end-stage renal disease secondary to adult polycystic kidney disease. Open surgical techniques remain the gold standard, although minimally invasive methods have gained traction in recent years. Native nephrectomy is frequently needed secondary to size or symptoms. Continued developments in surgical technology have allowed for the introduction of computer-assisted surgery (Robotics). We aim to describe the feasibility, safety, and efficiency of simultaneous laparoscopic bilateral nephrectomy and robotic-assisted kidney transplantation to treat end-stage renal kidney transplantation secondary to polycystic kidney disease. In this initial experience, 3 patients underwent kidney transplantation with a simultaneous bilateral nephrectomy. All patients tolerated the procedure well with no postoperative blood transfusions, dialysis, or surgical site infections. Simultaneous laparoscopic bilateral nephrectomy and robotic-assisted kidney transplantation may be feasible, safe, and efficient techniques. Complications were minimal, with short hospital stays. Supplemental Video; http://links.lww.com/TXD/A352